2023
DOI: 10.4085/616.21
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Myotonometry in Musculoskeletal Rehabilitation and Human Performance Programming

Abstract: Myotonometry is a relatively novel method used to quantify the biomechanical and viscoelastic properties (stiffness, compliance, tone, elasticity, creep, and mechanical relaxation) of palpable musculotendinous structures with portable mechanical devices called myotonometers. Myotonometers obtain these measures by recording the magnitude of radial tissue deformation that occurs in response to the amount of force that is perpendicularly applied to the tissue through a device’s probe. Myotonometric parameters suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“… Valderrabano et al (2007) and Bravo-Sánchez et al (2019) pointed out that habitually loaded activities induce changes in the structural and mechanical properties of athletes’ tendons and muscles, especially between the dominant and non-dominant side limbs. Most sports-induced injuries are overuse injuries, mainly manifested as contractures or muscle shortening, characterized by increased muscle tension and stiffness in addition to changes in muscle elasticity ( Iwata et al, 2019 ; McGowen et al, 2023 ). For example, a prospective study of lower limb stiffness and injury incidence among elite netball players found that during the season, the mean quasi-static stiffness of the soleus muscles and Achilles tendon of injured elite players was significantly higher than that of the uninjured elite players ( Pickering Rodriguez et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… Valderrabano et al (2007) and Bravo-Sánchez et al (2019) pointed out that habitually loaded activities induce changes in the structural and mechanical properties of athletes’ tendons and muscles, especially between the dominant and non-dominant side limbs. Most sports-induced injuries are overuse injuries, mainly manifested as contractures or muscle shortening, characterized by increased muscle tension and stiffness in addition to changes in muscle elasticity ( Iwata et al, 2019 ; McGowen et al, 2023 ). For example, a prospective study of lower limb stiffness and injury incidence among elite netball players found that during the season, the mean quasi-static stiffness of the soleus muscles and Achilles tendon of injured elite players was significantly higher than that of the uninjured elite players ( Pickering Rodriguez et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the MyotonPRO has been developed as a simple, non-invasive, lower-cost, reliable, and user-friendly tool, making it accessible to individuals with less technical expertise 11 . It is an effective method for assessing muscle mechanical properties when compared to other methods, such as TMG 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated different practicable approaches for determining tendon stiffness and length. Myotonometry-based approaches have been established concerning stiffness ( 8 ). Myotonometry is an indirect and non-invasive method that is based on the analysis of the deformation and oscillations of soft biological tissues induced by a short mechanical impulse applied perpendicular to the tissue surface ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Myotonometry-based approaches have been established concerning stiffness ( 8 ). Myotonometry is an indirect and non-invasive method that is based on the analysis of the deformation and oscillations of soft biological tissues induced by a short mechanical impulse applied perpendicular to the tissue surface ( 8 ). A frequently used instrument for objective measurements is the MyotonPRO digital palpation device ( 9 , 10 ), which has the highest estimated intraclass correlation coefficient (ICC), ranging from .94 to .98, compared to other handheld devices for measuring the stiffness of different layers in a phantom tissue model ( 11 ).…”
Section: Introductionmentioning
confidence: 99%